Food in time and place : the American Historical Association companion to food history - Freedman, Paul, 1949-; Chaplin, Joyce E.; Albala, Ken, 1964- (University of California Press, 2014)
Food and cuisine are important subjects for historians across many areas of study. Food, after all, is one of the most basic human needs and a foundational part of social and cultural histories. Such topics as famines, food supply, nutrition, and public health are addressed by historians specializing in every era and every nation. Food in Time and Place delivers an unprecedented review of the state of historical research on food, endorsed by the American Historical Association, providing readers with a geographically, chronologically, and topically broad understanding of food cultures-from anci.